PHONOLOGICAL ANALYSIS OF ERHUAYUN(儿化韵) IN MANDARIN - Rizki Utami; Nunung Supriadi (Bambuti, 2022)
Abstract. In Mandarin there is a suffix that causes a phonological process, namely in the word with the suffix addition to the suffix -r,called erhuayun (儿化韵). The purpose of this study was to analyze phonology in the word that has a suffix -r in Mandarin using a generative phonological approach. Data is obtained from Chinese subject books. The results in this study are in the word with the affix suffix -r divided into two, namely not experiencing phonological processes and experiencing phonological processes. Words that do not undergo phonological processes are in words with the sound suffixes /a/,/e/ and /u/. The phonological process that occurs in the word suffix -r is in the form of the addition of sound and sound absorption. The addition of sounds occurs when the sound /ü/ appears before the suffix -r. Sound suction occurs in words with the sound suffixes /n/, /ŋ/, /I/ and /o/. Phonological processes are described using distinctive feature rules.